Cellular Transplantation Alters the Disease Progression in Becker’s Muscular Dystrophy - Alok Sharma; Amruta Paranjape; Hemangi Sane; Khushboo Bhagawanani; Nandini Gokulchandran; Prerna Badhe (Case Reports in Transplantation)
Becker’s Muscular Dystrophy (BMD) is a dystrophinopathy manifested as progressive muscle degeneration. Autologous Bone Marrow Mononuclear Cells (BMMNCs) have shown some myogenic potential. The paracrine effects of the BMMNCs reduce the inflammation and are thought to reduce muscle degeneration. We treated a 39 year old dental surgeon suffering from BMD. Muscle strength was reduced when measured using modified Medical Research Council’s Manual Muscle Testing (mMRC-MMT). Static sitting balance was poor. He was wheelchair dependent for ambulation and moderately independent in Activities of Daily Living (ADL). Functional Independence Measure (FIM) score was 93. Musculoskeletal Magnetic Resonance Imaging (MRI-MSK) showed moderate fatty infiltration in the muscles. Three cellular transplantations were carried out. Clinical assessment and the investigations were repeated. Progressive increase in the muscle strength was noted. Ambulation was independent using push-knee splints and minimal assistance when weary. Static and dynamic balance in sitting and standing improved. FIM score increased from 93 to 105. There was no increase in the degree of fatty infiltration, as seen on the MRI-MSK. The case study provides evidence for the putative benefits of cellular therapy in altering the disease progression in BMD. It also suggests augmented clinical benefits of combination of cellular therapy and rehabilitation.